Use of GIS Technology as a Tool for Locating Public Libraries - Siyambalapitiya, S.C.D.; Gamage, Ruwan (University of Vocational Technology, 2021)
Due to its versatile nature, GIS provides a vast platform for the managers in decision making. GIS can be used in the management of public libraries too. Public libraries play a major role in the development process by upgrading educational levels in general and the literacy level in particular. Sri Lanka has 1199 public libraries. However, the public libraries must be correctly located in order to cater to the society at large with the notion that no any segment of the society could be marginalized in terms of access to information, and each citizen has the right to access information without being discriminated. It is believed that public libraries are publicly utilized when they are located in the correct places wherever deserved. This paper is aimed at analysing some key literature findings which forms only a part of a bigger research area, addressing the question whether public libraries are accessible to the population in local authority domain areas of the Uva province. The study fulfilled this knowledge vacuum by using GIS technology in locating public libraries. The Uva province was selected for the study considering its socio-economic status with the minimum provincial population in education attainment, low literacy rate and poverty incidence. Through this study, the service areas of public libraries in the Uva Province were identified and this will help most of the users to use this service qualitatively.
Keywords: GIS; Library Management; Location-Allocation; Public Libraries